Managing Assets Quality by Indian Commercial Banks in the Post Financial Crisis Period of 2008: - (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Financial sector plays an important role for the development of any economy. They channelize the idle cash into a productive use. Credits are made available to the borrowers on the basis of some basic principles i.e. credibility, capacity and collateral securities. When bank ignores these principles and offered loan without credit risk rating, it is the case of sub-prime lending. Excessive use of innovative financial product with the greed to earn more profit lead to the economic crisis in 2008. Financial crisis works as a speed breaker in the process of economic growth. Due to subprime lending in 2008, NPAs started shooting up, leading to stacking of poor quality assets on bank’s balance sheet. Stacking up of poor quality assets, due to subprime lending (NPAs) is the threat to banks survival. As, the financial stability of any bank depends upon assets quality on balance sheet. If NPA is less, bank would be in a sound financial position and vice-versa. However, Indian banking system is considered to be sound, well regulated, diversified and shock absorbing, even though due to globalization, Indian financial system was not immune to the financial crisis of 2008. As significant rise in NPAs could be observed on balance sheets of Indian banks. The NPA should be controlled and lessened, to enhance the profitability and efficiency of banks.